Study on the application of coal blending technology based on quantum particle swarm optimization in large circulating fluidized bed boiler. (October 2019) - Cai, B; Qin, T; Han, Y; Yv, Y L; Gao, Z P; Zhao, Z Y
Abstract: Based on the theory of quantum particle swarm optimization, the calculation method of coal characteristics is integrated. The calculation analysis model and theoretical method are put forward to determine the distribution characteristics of lignite blended coal parameters. The CFB furnace heat transfer model with partitioned section calculation and the overall algorithm of boiler thermal calculation with sequential module iteration are applied to carry out thermal calculation of mixed coal with different proportions of lignite coal and variable conditions. The influence rule of the parameters is analyzed, and the range of reasonable mixing ratio is 50 ∼ 70%. Based on the theory of combustion air dynamics and clean combustion theory, the performance of a large CFB boiler with high proportion of lignite burning is optimized, and the thermal efficiency of the boiler is increased to 90.845%. The power consumption of the integrated plant is reduced to 10.59 - 11.23%